New Methods and Old Issues: Theoretical and Methodological Approaches to Social Network Sites in the Arab Region - Layadi, Nacer-Eddine (ALBAHITH ALALAMI, 2013)
This paper critically looks at the studies that investigated the Social Network Sites in the Arab region asking whether they made a practical addition to the field of information and communication sciences or not. The study tried to lift the ambiguity of the variety of names, as well as the most important theoretical and methodological approaches used by these studies highlighting its scientific limitations. The research discussed the most important concepts used by these studies such as Interactivity, Citizen Journalism, Public Sphere, and Social Capital and showed the problems of using them because each concept comes out of a specific view to these websites. The importation of these concepts from a cultural and social context to an Arab Islamic environment raises so many issues and problems.